Simultaneous adsorption of pollutants onto the adsorbent review of interaction mechanism between the pollutants and the adsorbent - Girish, C. R. (International Journal of Engineering and Technology, 2026)
The contamination of the environment by the release of wastewater containing multi pollutants is one of the major environmental concern in the recent time. Adsorption using the adsorbent is an effective method for the removal of various pollutants from wastewater. In the simultaneous adsorption of a binary solution, the interaction among the pollutant molecules and the competition among the solutes for the adsorbent are complicated. Thus, it is important to understand the mechanism of the simultaneous adsorption of pollutants from the industrial point of view. Therefore the current work reviews the simultaneous adsorption of solutes from wastewater using different adsorbents. The interaction among the pollutants such as synergistic, antagonistic and non-interaction was determined. Different concepts used for understanding the interaction mechanism among the components and the adsorbent were discussed. The possible reason for the interaction formed among the pollutants is also investigated.